Synthesis and Antibacterial Activities of 2-Triazolinyl Quinoxalines - Pillai, P.M.; Mohan, Keshav (Asian Journal of Chemistry, 2010)
Reaction of 2-(aryliminomethyl) quinoxalines (1a–d) with diazomethane gave 2-(aryl-1,2,3-triazolin-5-yl) quinoxaline (2a–d) in good yield.